PENGARUH PELAYANAN TERHADAP KINERJA USAHA RUMAH MAKAN JUNILA DI KELURAHAN PASAR TELUKDALAM - Laia, Asamuri (Universitas Nias Raya, 2025)
The purpose of this study was to determine the effect of service on the business performance of Junila restaurant in Pasar Telukdalam Village. This type of research is a quantitative type of causal nature. The source of the data is from consumers who buy at Junila restaurant in Pasar Telukdalam Village. The data collection technique in this study is a closed questionnaire technique. The data analysis technique used is a simple linear regression analysis with a value of Y = 22.737 + 0.367X. Based on the results of hypothesis testing research with a calculated value of 3,107>ttable 1,672, it means that there is an influence of service on the business performance of Junila restaurant in Telukdalam Market Village. The suggestions of this study are (1) Junila restaurant should be able to provide services for consumers to improve business performance when making purchases. (2) In increasing customer satisfaction, employees should provide good service to consumers through a friendly attitude so that consumers are loyal on the spot. (3) To maintain consumers making purchases at Junila restaurants, the products sold by Junila restaurants should be adjusted to their daily needs.